BEHÇET'S DISEASE WITH GASTRIC ACCOMMODATION - CASE REPORT (CIPEEX, 2022)
BEHET'S DISEASE (DB) IS A SYSTEMIC INFLAMMATORY VASCULITIS OF CHRONIC CHARACTER AND RARE OCCURRENCE, CHARACTERIZED MAINLY BY RECURRENT EPISODES OF ORAL APHTHOUS ULCERS, GENITAL ULCERS, OCULAR LESIONS AND OTHER MANIFESTATIONS, INCLUDING SKIN LESIONS, VASCULAR, GASTROINTESTINAL AND EVEN ALTERATIONS. NEUROLOGICAL INVOLVEMENT. ITS PREVALENCE IS HIGHER IN COUNTRIES ALONG THE OLD "SILK ROAD", BUT MAY PRESENT A WIDE GEOGRAPHICAL VARIATION. THE OBJECTIVE OF THIS STUDY IS TO REPORT AN ATYPICAL CASE OF BEHET'S DISEASE AND TO COMPARE IT WITH THE LITERATURE IN ORDER TO HIGHLIGHT IMPORTANT PECULIARITIES FOR MEDICAL PRACTICE. THIS IS A CASE OF A PATIENT DIAGNOSED WITH BEHET'S DISEASE TEN YEARS AGO WHO, AT THE BEGINNING, PRESENTED URTICARIAL LESIONS THROUGHOUT THE BODY, IN ADDITION TO ORAL AND GENITAL ULCERS. HOWEVER, HE RECENTLY SOUGHT OUT THE GASTROENTEROLOGY CLINIC DUE TO SEVERE PAIN IN THE EPIGASTRIC REGION, BEING TAKEN TO PERFORM AN UPPER GASTROINTESTINAL ENDOSCOPY URGENTLY, SHOWING A WALL ISCHEMIA IN GREAT CURVATURE OF THE GASTRIC BODY. CORRELATING THE LITERATURE WITH THE CASE PRESENTED, WE CAN SEE AN ATYPICAL EVOLUTION OF A DISEASE OF LOW INCIDENCE IN BRAZIL, SINCE THE GASTROINTESTINAL INVOLVEMENT IS NOT SO COMMON IN PATIENTS WITH BEHET'S DISEASE. THUS, THE PRESENTATION OF THIS CASE BECOMES EXTREMELY IMPORTANT, SINCE IT AIMS TO ALERT HEALTH PROFESSIONALS ABOUT THE OCCURRENCE OF SERIOUS AND RARE COMPLICATIONS OF BEHET'S DISEASE IN THE DIGESTIVE TRACT.
Keywords: Behçet's syndrome. Vasculitis. Vascular Diseases.